Penetration and Activation of Brain Endothelium by Salmonella enterica Serovar Typhimurium - van Sorge, Nina M. (Oxford University Press, 2011)
Salmonella meningitis is a serious disease of the central nervous system, common particularly in Africa. Here, we show that Salmonella enterica serovar Typhimurium is able to adhere, invade, and penetrate human brain microvascular endothelial cells (hBMECs), the single-cell layer constituting the blood–brain barrier (BBB). Cellular invasion was dependent on host actin cytoskeleton rearrangements, while expression of a functional type III secretion system was not essential. In addition, Salmonella infection activated a proinflammatory immune response targeting neutrophil signaling and recruitment. Salmonella invasion and immune activation may represent a crucial step in the penetration of the BBB and development of Salmonella meningitis.